2021
DOI: 10.1177/00031348211048844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroidectomy on Normocalcemic Primary Hyperparathyroidism and the Role of Intraoperative PTH Measurement

Abstract: Background Normocalcemic primary hyperparathyroidism (NCpHPT) and normohormonal primary hyperparathyroidism (NHpHPT) are recently recognized variants of primary hyperparathyroidism. Current guidelines for the management hyperparathyroidism recognize NCpHPT as one of the areas that are recommended for more research due to limited available data. Methods A retrospective review of patients who had parathyroidectomy between 2014 and 2019. We excluded patients with multiple endocrine neoplasia syndromes and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Hence conventional imaging modalities could have a suboptimal detection rate in this subset of cases. Ehab Alameer et al reported more negative sestamibi scans significantly in nPHPT (8.2% vs. 51.3%, p < .01) than hypercalcemic PHPT 23 . Cunha‐Bezerra et al showed better performance of 4DCT (44.4%) compared to USG (22.2%) and scintigraphy (11.1%) in nPHPT patients for accurate localisation of abnormal glands 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Hence conventional imaging modalities could have a suboptimal detection rate in this subset of cases. Ehab Alameer et al reported more negative sestamibi scans significantly in nPHPT (8.2% vs. 51.3%, p < .01) than hypercalcemic PHPT 23 . Cunha‐Bezerra et al showed better performance of 4DCT (44.4%) compared to USG (22.2%) and scintigraphy (11.1%) in nPHPT patients for accurate localisation of abnormal glands 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies suggest that parathyroidectomy for nPHPT results in comparable biochemical cure rates as hypercalcemic PHPT (hPHPT) [6]. However, as recent publications have become more rigorous in the diagnosis of nPHPT, some have highlighted that large proportions of nPHPT patients actually do not achieve biochemical cure after surgery, as defined as normalization of PTH levels by 6 months postoperatively [7,8]. Furthermore, while it has been shown that parathyroidectomy has long-term benefits in bone mineral density (BMD) in hPHPT patients, and it remains unclear whether these benefits are seen in nPHPT patients [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Did they use Intra Operative PTH monitoring in their cohort of nPHPT? [4]. If so what was the result and what criteria did they use?…”
mentioning
confidence: 99%